Implementasi Metode Naïve Bayes Dalam Sistem Pakar Diagnosis Penyakit Pada Itik Mojosari - Andreswari, Desi; Suteky, Tatik; Epana Sari, Renti (Universitas Bengkulu, 2024)
Mojosari ducks are a type of duck that has potential as an egg producer, so many duck breeders are interested in it. Delays in treating disease in Mojosari ducks can result in various losses, such as decreased egg quality and quantity, disease transmission to other ducks, and can cause death of the ducks. Therefore, researchers built an expert system that can carry out quick and accurate diagnoses of duck diseases as well as correct countermeasures. This system was built by applying the Naïve Bayes method to an expert system to diagnose Mojosari duck disease by calculating the prior probability value of each disease based on input of symptoms that appear in the ducks. This system can detect 10 types of diseases and 40 symptoms that attack Mojosari ducks. This research was carried out with 30 test data and resulted in a system accuracy of 90%. Keywords: Mojosari Ducks, Diseases, Diagnose, Ducks, Expert Systems, Naïve Bayes.